2017
DOI: 10.1136/bjsports-2016-097108
|View full text |Cite
|
Sign up to set email alerts
|

The effects of shoe-worn insoles on gait biomechanics in people with knee osteoarthritis: a systematic review and meta-analysis

Abstract: Objectives The effect of shoe-worn insoles on biomechanical variables in people with medial knee osteoarthritis has been studied extensively. The majority of research has focused specifically on the effect of lateral wedge insoles at the knee. The aim of this systematic review and meta-analysis was to summarise the known effects of different shoe-worn insoles on all biomechanical variables during level walking in this patient population to date. Methods Four electronic databases were searched to identify studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 45 publications
1
51
1
Order By: Relevance
“…The lateral wedge insole used for knee OA patients was reported to significantly increase the amount of ankle/subtalar joint complex, resulting in lateral shift of the COP and reduction of KAM. However, accentuation of rearfoot pronation in already pronated feet could potentially result in higher talofibular contact pressure, causing ankle symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral wedge insole used for knee OA patients was reported to significantly increase the amount of ankle/subtalar joint complex, resulting in lateral shift of the COP and reduction of KAM. However, accentuation of rearfoot pronation in already pronated feet could potentially result in higher talofibular contact pressure, causing ankle symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In people with medial knee OA, a number of studies have shown that lateral wedge insoles [15], flat flexible shoes [16], and shoes with midsoles that are stiffer laterally than medially redistribute knee load away from the medial TF compartment towards the lateral compartment [17], albeit clinical effects are uncertain [18]. This is achieved via a lateral shift in the frontal plane ground reaction force-knee joint centre lever arm [19,20] and an increase in lateral plantar pressures [21].…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic knee OA has been shown to be in uenced by both biomechanical and neuromuscular treatments, which has led to conservative treatments currently available largely aim to in uence either one of these factors (20)(21)(22)(23)(24)(25)(26)(27). Interventions typically attempt to manipulate the KAM and KAAI loads transmitted through the joint, or improve the neuromuscular de cits seen within the pathology by muscle strengthening and proprioceptive exercises (28,29).…”
Section: Introductionmentioning
confidence: 99%